Heat and mass transfer modeling for multicomponent multiphase flow with CFD - Padoin, Natan; Dal’Toé, Adrieli T.O.; Rangel, Leonardo P.; Ropelato, Karolline; Soares, Cíntia (International journal of heat and mass transfer, 2014)
Heat and mass transfer take place in a large number of processes. These phenomena are encountered in systems comprised of two or more phases, in which at least one of them is a mixture of many chemical species. The predictability of such multiphase and multicomponent systems plays a major role in the efficient design and operation of equipment and processes, where CFD has been frequently applied successfully over the past decade. Modeling multicomponent flow remains a challenge in relation to both micro or macro systems. In this study, simulations were carried out with the commercial code ANSYS® CFD (FLUENT®), version 14.0, and customized functions developed to predict the equilibrium compositions and temperature of a vapor–liquid system. A preliminary study on a binary mixture (water/air) was conducted in order to validate the results obtained with the commercial code using the data obtained from a standard psychrometric chart. In addition, simulations were carried out for a mixture of four pure hydrocarbons (methane, n-pentane, n-hexane and n-octane). Thus, a complete multicomponent mass transfer theory, based on Maxwell–Stefan’s equations, was applied as a customized function code, which can be used to calculate high flux corrections and the convective mass flux. The results were verified with predicted values obtained using the steady-state process simulator PRO/II®, version 8.2.